EPISTEMOLOGI INTELIJEN DALAM NARASI NEGARA YANG BIAS TENTANG GERWANI DALAM G30S 1965 - Firyasa, Nadilya Adhwari; Adian, Donny Gahral; Mukhlis, Meutia Irina (UI Scholars Hub, 2025)
This study analyzed epistemic bias in the state’s narrative about Gerwani during the 1965 G30S event using the epistemology of intelligence approach. Through a qualitative philosophical method, this research evaluated the state’s processes of information acquisition, interpretation, and dissemination, focusing on the identification of political bias, gender bias, confirmation bias, framing effects, overconfidence bias, as well as the use of misinformation and disinformation. The findings revealed that the state’s narrative about Gerwani was systematically constructed to support the New Order regime’s political agenda through the manipulation of information. These biases led to dangerous epistemic failures and justified violence and the erasure of women’s historical roles. The study concluded that a Pancasila-based philosophy of intelligence, especially the epistemology of intelligence, was necessary to prevent future misuse of intelligence practices. It was recommended that state intelligence agencies prioritize truth, justice, and human rights principles to create an ethical and accountable intelligence system aligned with democratic values.